Improving Students Islamic Behavior through Teacher Prophetic Education Model - Kurniawan, Naufal; Limei, Sun; Catherine, Sarkissian (International Journal of Educational Narratives, 2023)
Background. Learning begins with providing pretest questions to find out the extent of student learning activities. Experimental students were given learning using the small group discussion method while the control group used conventional learning methods. Purpose. This study used the descriptive qualitative method. Researchers collected data by using in-depth interviews, participant observation, and documentation. Method. While the data analysis technique used interactive analysis, with the stages of data collection, data editing, and data presentation. Results. The results of this study: 1) that the efforts of the aqidah moral teacher in improving the Islamic behavior of students by holding religious activities such as holding regular monthly recitations, increasing students' awareness by living clean, setting good examples, providing classical guidance; 2) Obstacles in improving the Islamic behavior of students from environmental factors, and parents; 3) how to overcome obstacles in improving the Islamic behavior of students by giving punishment and collaborating with boarding school administrators and parents of students. Conclusion It was proveb by the calculation of N-gain of 0,76 with category.